Being Comfortable with the Uncomfortable: Tips for Addressing Conflict - Christopher Jochum (Academic Chairpersons Conference Proceedings, 2019)
In this session, the topic of conversation will focus on how to effectively address conflict with both faculty, staff and students. The facilitator will offer proven-tips he’s used as a department chair, which were gleaned and/or developed in consultation with mentors, colleagues and even legal counsel.
Keywords: Departmental leadership; Conflict management; Students; Faculty; Staff